Shadow rate as a measure of unconventional monetary policy in the euro area - Honkavaara, Iines (My University, 2022)
The interest rates in the euro area have remained negative or near the zero lower bound during the past decade, which has caused the European Central Bank to resort to various means of unconventional monetary policy. This creates significant challenges for traditional econometric models assessing the impact of monetary policy, as the policy rate no longer captures the effects of the new monetary policy measures. A possible tool to accommodate the zero lower bound in an econometric model is a shadow short rate, which is a statistical tool to summarize the monetary policy stance of the central bank. We employ a shadow short rate in a standard vector autoregressive framework to compare the shadow short rate with the standard policy rate. Our analysis shows that the shadow short rate exhibits similar dynamics with inflation and unemployment as the standard policy rate does. The magnitude of the monetary policy shocks identified from both interest rates are similar. The shadow short can therefore be substituted for the standard policy rate in vector autoregressive analysis.

Finanssikriisin 2008 jälkeen euroalueen korkotaso on pysytellyt lähellä nollan tuntumaa tai jopa negatiivisena. Matalan korkotason vuoksi Euroopan keskuspankki on joutunut turvautumaan epätavanomaisen rahapolitiikan keinoihin, kuten keskuspankkitaseen kasvattamiseen. Tämä aiheuttaa huomattavia haasteita perinteisten ekonometristen mallien käyttämiseen rahapolitiikan vaikutusten arvioinnissa, sillä keskuspankin asettama ohjauskorko ei enää ole riittävä rahapolitiikan mittari. Mahdollinen keino adaptoida nollakorot ekonometrisissa malleissa on niin kutsuttu varjokorko, joka on tilastollinen työkalu keskuspankin rahapolitiikan havainnollistamiseksi. Tutkielmassa käytetään hyväksi varjokorkoa tavanomaisessa vektoriautoregressiomallissa vertaillakseen varjokorkoa ja ohjauskorkoa. Tutkielman keskeisenä tuloksena on, että varjokorolla ja ohjauskorolla on samankaltaisia dynaamisia vaikutuksia inflaation ja työttömyyden kanssa. Estimoitujen rahapolitiikkashokkien vaikutus muihin muuttujiin on suunnilleen yhtä suuri kumpaakin korkoa hyödyntäessä. Varjokorkoa voi siis hyödyntää ohjauskoron sijaan vektoriautoregressiomallissa.
Keywords: unconventional monetary policy, vector autoregression, shadow rate term structure modelling